ASPECTELE FINANCIARE ALE ECONOMIEI CIRCULARE - Filip, Angela (CEP USM, 2022)
A large number of experts have recently come to the conclusion that the circular economy has become a symbol of progressive civilization and of the plea for the rational use of resources. This aims to change the classic (linear) model of the economy, insisting on products and services capable of substantially reducing waste and environmental pollution. The circular economy presupposes a particular system of thinking and human activity, a particular culture of consumption and production, and maximum rationality. Specialists in the examined field consider the implementation of the circular economy model in the largest part of the world's countries towards the year 2030 a vital necessity at the global level. Apart from the economic effects and the reduction of pollution in important proportions, this can result in substantial additional profits. One of the conditions for these economic transformations is the respective adjustment of banking and investment activity. Following the study of the different opinions of researchers in the addressed field, as well as the statistical, economic and financial trends published in different informational sources, this article comes with a synthetic picture of the financial aspects of the circular economy
Keywords: circular economy